Digital transformation of enterprises: trends, factors, results - Zakharov, Vladimir; Ludushkina, Elena; Kislinskaya, Marina; Kornilova, Elena; Novikov, Alexey (Nexo Revista Científica, 2022)
Goals. To identify methodological contradictions and inconsistencies between different approaches to measuring the digital economy as a whole, the digital transformation of enterprises; to assess the effectiveness of digital transformations, and to outline the contours of the modern paradigm of digital transformation management in the post-Covid world. Results. The changes in the conceptual approaches to the measurement of the digital economy and digital transformation due to new trends in the development of digital transformation have been revealed. It has been shown which factors and actions determine the results of the digital transformation of enterprises, based on which the modern paradigm of digital transformation management has been formed. The features of the national digital transformation strategy have been analyzed. Conclusion. In the new post-Covid reality, enterprises will change dramatically, and to achieve success they will need a new paradigm of digital transformation management, organically combining economic and social aspects, a strategic and operational approach, considering transformation management as a flexible self-learning ecosystem.